Social Innovation In Education: The Experience Of Uzbekistan And The United States (Journal of Pedagogical Inventions and Practices, 2026)
This article examines social innovation in education through a comparative analysis of the experiences of Uzbekistan and the United States. Education is considered as a socially conditioned institution that reflects cultural values, historical traditions, and contemporary societal needs. The study aims to identify key socially innovative ideas and practices implemented within the educational systems of both countries, as well as to analyze the factors influencing their development and effectiveness. Using a comparative and interdisciplinary approach, the article explores how social, cultural, and policy-related contexts shape educational reforms and innovative initiatives. Special attention is paid to the role of education in fostering social inclusion, civic engagement, and the adaptation of educational systems to modern challenges. The findings demonstrate that, despite differences in historical and sociocultural backgrounds, both Uzbekistan and the United States employ education as a strategic tool for social development and innovation.